INVENTARISASI BINTANG LAUT (ECHINODERMATA: ASTEROIDEA) DI PANTAI PULAU PARI, KABUPATEN ADM. KEPULAUAN SERIBU - Narti Fitriana (Faktor Exacta, 2010)
The study about diversity of starfish at Pari Island Beach had been done at November 20 up to 22nd 2009. This aim to know diversity of starfish species at Pari Island Beach by using descriptive method. Sample collected by using 5 belt transect, one belt transect and other is 20 m distance and 100 m length. Base on my research, we found 2 species of starfish, there were Asterias sp. and Culcita sp. Asterias sp. is dominant species but not for Culcita sp. This spesies is very rare because just 1 individual we can find along this transect observation. Keywords: asteroidea, culcita, starfish, pari, belt transect